Qualitative Analysis of the Perceived Value of Repeat Visits at the Wonokromo Traditional Market in Surabaya - Auliyah, Ruodlotul (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The research aims to determine the role of perceived value in the intention to revisit the Wonokromo Traditional Market, Surabaya. This study used qualitative research methods. As in the stages of conducting observations, interviews, and documentation. The data source was obtained when conducting direct research at the Wonokromo Traditional Market, Surabaya. The research results show that the analysis of perceived value in intention to revisit the Wonokromo Surabaya Traditional Market looks at quality, emotional, price, and social value. The presence of new visits by visitors, because they received information from previous visitors’ experiences, is evidence that visitors get a high level of satisfaction with their shopping experience, which is then realized through recommendations for visits for new visitors. Theoretically, the findings of this research contribute to the understanding of the multifaceted nature of perceived value in the context of traditional markets, emphasizing the interconnected roles of quality, emotional, price, and social values. Additionally, the observed phenomenon of new visits driven by positive word-of-mouth and shared experiences underscores the significance of social influence in shaping consumer behavior, suggesting that the perceived value not only influences individual intentions but also propagates through social networks, highlighting the broader social implications of consumer satisfaction and recommendation behaviors in traditional market settings.